Algorithms and data structures proceedings - Dehne Frank ed.; International Workshop, WADS 2005 on Algorithms and Data Structures; International workshop, WADS 2005 on algorithms and data structures Waterloo, Canada 15-17 Aug 2005 (Berlin Springer-Verlag, 2005)
A broad variety of topics in algorithmics and data structures is addressed in this book including searching and sorting, approximation, graph and network computations, computational geometry, randomization, communications, combinatorial optimization, scheduling, routing, navigation, coding, and pattern matching.
Keywords: Computer algorithms; Data structures